Different amount of carboxyl-aldehyde fractionated nanofibril cellulose and main characteristics of chitosan, gelatin, alginate added composites - Kurtuluş, Orçun Çağlar; Ondaral, Sedat; Emin, Nuray; Aşıkuzun, Elif (Elsevier BV, 2023)
In this research, two different types of nanofibrillated celluloses (NFCs) having different amounts of aldehyde and carboxyl groups were mixed with chitosan (CH), gelatin (GL), and alginate (AL) with different mixing ratios to produce biocomposite aerogels. There was no related study in the literature about producing aerogels with the addition of NC and mentioning biopolymers in addition to the effect of carboxyl and aldehyde fraction of the main matrix NC on composite properties. For this purpose, the main aim of this study was to investigate how carboxyl and aldehyde groups affect the basic characteristics of NFC-biopolymer based materials addition to efficiency of biopolymer amount in main matrix. Even after preparing homogenous NC-biopolymer compositions at 1 % concentration with varied proportions (75 %-25 %, 50 %-50 %, 25 %-75 %, 100 %), aerogels were still made using the fundamentally easy lyophilization procedure. Porosity values for NC-Chitosan (NC/CH) based aerogels range from 97.85 to 99.84 %, whereas those made from NC-Gelatin (NC/GL) and NC-Alginate (NC-AL) have values of 99.2-99.8 % and 98.47 to 99.7 %, respectively. In addition, densities were determined in the range of 0.01 g/cm3 for both NC-CH and NC-GL composites, but higher values were obtained in ranged between 0.01 and 0.03 g/cm3 for NC-AL samples. The crystallinity index values showed a decreasing trend with the addition of biopolymers into NC composition. SEM images showed that all materials have a porous micro structure with different size pores and homogenous surface topography. As a result of the specified tests, these materials can be used in many different industrial applications, such as dust collectors, liquid adsorbers, specific material for packaging and medical materials.
Keywords: Chitosan; Aldehydes; Biopolymers; Alginates; Gelatin; Cellulose